1999
DOI: 10.1093/nar/27.24.4807
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a gene encoding human Kruppel-like factor 5 (IKLF): binding to the CAAT/GT box of the mouse lactoferrin gene promoter

Abstract: The mouse lactoferrin gene promoter includes a CAAT/GT box, GGGCAATAGGGTGGGGCCAGCCC, which functions as the epidermal growth factor response element (EGFRE) in human endometrial carcinoma RL95-2 cells (RL95). A positive clone, EGFREB, of 2575 bp length, was isolated from an expression library of RL95 cells with a multimer of the EGFRE sequence. In this work, we have identified that EGFREB encodes the C-terminus of Kruppel-like factor 5 (KLF5). This mRNA is most abundant in human colon and small intestine. A fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 0 publications
5
54
0
Order By: Relevance
“…In agreement with the luciferase results described above, the wild-type (wt), but not the mutant, biotinylated oligonucleotides from the FGF-BP promoter efficiently pull down the KLF5 protein overexpressed in MCF7 (Figure 4c, left). Interestingly, the wt oligonucleotides from the FGF-BP promoter pull down even more KLF5 than the positive control oligonucleotides from the mouse lactoferrin gene (Shi et al, 1999). These results were confirmed by a competition assay (Figure 4c, right).…”
Section: Klf5 Promotes Cell Growth Through Fgf-bpsupporting
confidence: 54%
See 1 more Smart Citation
“…In agreement with the luciferase results described above, the wild-type (wt), but not the mutant, biotinylated oligonucleotides from the FGF-BP promoter efficiently pull down the KLF5 protein overexpressed in MCF7 (Figure 4c, left). Interestingly, the wt oligonucleotides from the FGF-BP promoter pull down even more KLF5 than the positive control oligonucleotides from the mouse lactoferrin gene (Shi et al, 1999). These results were confirmed by a competition assay (Figure 4c, right).…”
Section: Klf5 Promotes Cell Growth Through Fgf-bpsupporting
confidence: 54%
“…The mutant oligonucleotide sequence is 5 0 -CGG CTCCCTCGAAGAGACTTGGCTGGGAGG-3 0 . An oligo (5 0 -GATCGGGCAATAGGGTGGGGCCAGCCC-3 0 ) binding to KLF5 was used as a positive control (Shi et al, 1999).…”
Section: Dual Luciferase Assaymentioning
confidence: 99%
“…6) which prevents nuclear translocation of NF-ÎșB suggesting that a NF-ÎșB binding element is present in the mouse LF promoter. Recently, Kruppel-likefactor 5 (KLF5), a member of the Kruppel-like factors family of transcription factors [43,44] which we have cloned and identified as a mouse LF mitogen response unit (MRU) binding protein [45], was thought to be an important mediator for LPS-induced proinflammatoy response in intestinal epithelial cells [40]. Therefore, LPS could activate LF expression by enhancing the expression or activity of KLF5 in HC-11 cells.…”
Section: Discussionmentioning
confidence: 99%
“…By using the inhibitors we showed that JNK and p38 MAPK, and PKC pathways are indeed involved in LPS induction of LF expression in HC-11 cells. Previously, we found that transcription factors such as AP1, c-fos and c-jun, Sp1, Sp3 and KLF5 bind to the GT-box, AP1 and CRE binding elements of the mouse LF MRU and activate the transcriptional activity of the promoter [18,45,46]. These transcription factors could be recruited to mediate the MAPK and PKC signals activated by LPS exposure and stimulate the transcriptional activity of the LF gene.…”
Section: Discussionmentioning
confidence: 99%
“…This family of transcription factors is involved in several aspects of tumorigenesis, including growth control, apoptosis, and angiogenesis (Black et al, 2001). It has been demonstrated that KLF5 can bind to CACCC motifs and thereby regulate the expression of other genes (Conkright et al, 1999;Shi et al, 1999). Another member of this family, KLF4, is significantly downregulated during intestinal tumorigenesis (Ton-That et al, 1997).…”
Section: Discussionmentioning
confidence: 99%